The capacity to innovate : cluster policy and management in the biotech sector - Giest, Sarah, 1986- (Studies in comparative political economy and public policy., 2021)
"In The Capacity to Innovate, Sarah Giest provides insight into the collaborative and absorptive capacities needed to provide public support to local innovation through cluster organizations. The book offers a detailed view of the vertical, multi-level, and horizontal dynamics in clusters and cluster policy and addresses how they are managed and supported. Using the biotechnology field as an example, Giest highlights challenges in the collaborative efforts of public bodies, private companies, and research institutes to establish a successful eco-system of innovation in this sector. The book argues that cluster policy in collaboration with cluster organizations should focus on absorptive and collaborative capacity elements missing in the cluster context in order to improve performance. Currently, governments operate at different levels--local to supranational--in order to support clusters, and cluster policies are often pursued in parallel to other programs. As the book shows, this can lead to uncoordinated efforts and ineffective cluster strategies. Relational dynamics are often overlooked when working backwards from performance indicators, since their effects are largely indirect but Giest demonstrates that both the cluster organization and the cluster eco-system play a role. The Capacity to Innovate advocates for a coordinated effort by government and cluster organizations to support capacity elements lacking within the specific cluster context."--